Developing the foundations of a cognition-based human reliability analysis model via mapping task types and performance-influencing factors: Application to radiotherapy. (February 2018) - Pandya, Dhruv; Podofillini, Luca; Emert, Frank; Lomax, Antony J; Dang, Vinh N
Most human reliability analysis methods have been developed for nuclear power plant applications; this challenges the application of the available techniques to other domains. Indeed, for application to a specific domain, a human reliability analysis method should address the relevant tasks and performance conditions. The aim of this article is to propose a methodology to develop a generic task type–performance-influencing factor structure, specific for application to a domain of interest and directly linked to an underlying cognitive framework of literature. The structure provides the foundation of a human reliability analysis method built on the generic task type concept; it identifies the sector-specific performance-influencing factor effects on the failure probability that the method needs to represent and quantify for each generic task type. The methodology is intended to support a systematic and traceable process to develop the generic task type–performance-influencing factor structure, to ease the review of the process and of its results and, in case, identify and implement changes to the structure. The proposed methodology is applied to the radiotherapy domain allowing the development of sector-specific taxonomies of representative critical tasks, their failure modes, underlying cognitive failure mechanism, and influencing performance-influencing factors. This is part of a broader activity carried out by the Risk and Human Reliability Group at the Paul Scherrer Institute of Switzerland to develop a human reliability analysis method, specific for the radiotherapy domain. The activity is conducted in close cooperation with Paul Scherrer Institute's Center for Proton Therapy, where a first application of the method is foreseen.